CAREER INFORMATION SERVICES AS AN EFFORT TO DEVELOP CAREER EXPLORATION FOR STUDENTS AT THE MANAHIJUSSADAT ISLAMIC BOARDING SCHOOL - Nuroniah, Pepi; Fitriani, Yulianti; Sundari, Nenden; Tsabitha Saputra, Salwa (PT Altin Riset Publishing, 2025)
High school students are in the career exploration development stage. The acquisition of career information in Islamic Boarding Schools needs to be optimized. Career information is usually delivered by Guidance and Counseling teachers. This Community Service Program aims to introduce career information guidance services to students at the Manahijussadat Lebak-Banten Islamic Boarding School, as well as provide information on the registration mechanism at state universities to teachers. This activity is part of the implementation of Tri Dharma through a workshop that uses a question and answer technique. The participants were grade XII students and their supervising teachers. The activity methodology follows the A.P.P.L.E (Assess, Plan, Prepare, Lead, Evaluate) facilitation model. The description of the activity results is described based on the A.P.P.L.E. stages. The technique for collecting data on workshop participant satisfaction with the workshop implementation used questionnaires and interviews. Data analysis used descriptive quantitative analysis. The results of the workshop implementation of the community service program were students gaining knowledge on how to identify interests and talents to achieve their desired careers. This allows teachers to gain an understanding of the use of career information services. Participants' responses to the workshop ranged from satisfied to very satisfied, suggesting a continued program.